The role of color Doppler and spectral flow analysis in the management of pregnancy induced hypertension - Diwanji, Nehal S.; Pancholi, Alpesh D.; Shastri, Mona (International Journal of Research in Medical Sciences, 2017)
Background: Nearly one third intrauterine death of normally formed singleton fetuses are associated with IUGR coexisting with or without pregnancy induced hypertension (PIH). Abnormal fetal circulation is considered a major factor in fetal growth restriction, both as a cause and an indicator. Doppler ultrasound is a relatively new technique which merits investigations as a screening method for IUGR and PIH as both are associated with placental vascular pathology. The development of Doppler ultrasonographic technology, particularly during last 10 years, has provided an opportunity to obtain both qualitative and quantitative assessment of maternal and fetal hemodynamics using a non-invasive method. Objectives were to assess the role of color Doppler and spectral flow analysis in the management of pregnancy induced hypertension. Methods: It was a prospective observational study in which 50 pregnant women were taken as cases with pregnancy induced hypertension and 25 as matched controls without any high-risk factor. All patients were examined for colour Doppler spectral flow analysis. Detailed USG results in the form of maturity by biparietal diameter, head circumference, femoral length, abdominal circumference, liquor, and expected fetal weight were measured and noted. Doppler study of umbilical artery, fetal middle cerebral artery, both maternal uterine arteries and ductus venosus was carried out. Parameters in the form of resistive index (RI), pulsatility index (PI) and systolic/diastolic ratio (S/D) of all four arteries were taken. In ductus venosus waveform, changes in the ‘a’ wave were noted. All participants were followed up from the point of the recruitment up to the time of delivery. At the time of delivery, the mode of delivery, any complications, the Apgar score, weight of the baby, birth asphyxia and admission in NICU were noted. Results: The number of patients with PIH were highest in the age group of 21-25 years [n=31 (62%)]. IUGR of fetus occurred in 74% of the cases with PIH, while no any patients with IUGR fetus among the control group. 92% patients among uterine notches showed abnormal fetal outcome in the form of low birth weight, preterm delivery, LSCS for fetal distress, birth asphyxia or NICU admission of the neonate. Out of total 37 (74%) IUGR cases, 24 (65%) cases had fetoplacental Doppler abnormality. Out of total 6 cases with absent end-diastolic flow (AEDF) 4 cases had abnormal fetal outcome and 2 cases had delivered still-born babies. 20 out of 30 cases had abnormal fetal middle cerebral arterial Doppler (MCA) PI, out of which 19 patients had abnormal fetal outcome. 23 cases had abnormal CPR, out of them 20 (87%) cases had abnormal outcome and only 3 cases had normal fetal outcome. The parameters at the time of delivery are number of cases with delivery before 37 weeks of GA (63.3%), SGA babies (70%), LSCS for fetal distress (43.3%), and NICU admission (43.3%). Conclusions: Examining the maternal vessels using Doppler ultrasound, it is possible to determine the risk of complication developing in the course of pregnancy long before clinical signs of preeclampsia appear, so that therapeutic measures may be undertaken early.